(untitled) (Pulse, 2024)
Introduction: Hypokalemic periodic paralysis (HPP) is a rare neuromuscular disorder associated with episodes of hypokalemia induced muscle weakness and paralysis. There have been some studies that reported presence of cardiac arrhythmias, secondary to hypokalemia. Case Report: A 49-year-old hypertensive, diabetic lady presented to a specialized cardiac hospital with sudden transient weakness of both lower limbs along with palpitations, for last 3 hours. She also had an episode of transient loss of consciousness for 2-3 minutes, 30 minutes back. On examination, her pulse & blood pressure were non-recordable & patient was drowsy. ECG was recorded & monitor was attached immediately which showed ventricular tachycardia (VT). She was immediately given synchronized DC cardioversion for 2 times & she was reverted to sinus rhythm with restoration of consciousness. Her vitals were stable after cardioversion. Her neurological examination revealed hypotonia of her both lower limbs with diminished jerks and bilateral plantar flexor reflex. Her detailed history & previous records showed similar history of transient lower limb weakness with hospitalizations twice with hypokalemia within last 2 years. All those episodes occurred following heavy meals. After cardioversion, the rhythm was sinus but features were suggestive of presence of hypokalemia including prolonged QT. All baseline investigations were done & she was found to be severely hypokalemic (2.2 mmol/L) along with anemia, hyponatremia & hypomagnesemia. IV potassium & IV magnesium were given along with oral potassium supplementation. All workups were done to find out the cause of her recurrent hypokalemia. Finally diagnosis was made as a case of Hypokalemic Periodic Paralysis with VT. Conclusion: Although rare but hypokalemic periodic paralysis can present with malignant arrhythmias like VT. So ECG interpretation should be prompt along with prompt management. Pulse Vol.16, 2024 P: 34-37